2016
DOI: 10.1136/bjophthalmol-2016-308813
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomographic predictor of retinal non-perfused areas in eyes with macular oedema associated with retinal vein occlusion

Abstract: The presence of low reflective spaces in the RNFL in the OCT images can predict the presence of retinal non-perfused areas in eyes with macular oedema associated with a RVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Podkowinski found that all 3 different retinal compartment layers were thinner in the atrophy group than in the control group [ 20 ]. Hasegawa found that low reflective spaces in the retinal nerve fibre layer could predict full RT and inner RT thinning in BRVO patients [ 19 ]. Our findings indicate that necrotic or apoptotic changes of cells simultaneously happened in superficial and deep retinal layers due to a decrease in both SVC-VD and DVC-VD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Podkowinski found that all 3 different retinal compartment layers were thinner in the atrophy group than in the control group [ 20 ]. Hasegawa found that low reflective spaces in the retinal nerve fibre layer could predict full RT and inner RT thinning in BRVO patients [ 19 ]. Our findings indicate that necrotic or apoptotic changes of cells simultaneously happened in superficial and deep retinal layers due to a decrease in both SVC-VD and DVC-VD.…”
Section: Discussionmentioning
confidence: 99%
“…In the single linear regression model, we found that VA with complete resolution of MO was positively correlated with quadrantal SVC-VD, but not quadrantal DVC-VD. The reason might be apoptotic or necrotic changes of RNFL, which receives its blood supply from SVC and plays an important role in VA [ 19 ]. And the reason why we could not find a significant correlation between VA and DVC-VD might be the small sample in our study and the fluctuation of the nature of OCTA readings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furashova were observed in BRVO eyes after 2 years of follow-up and cannot be used in the acute phase. A recent study of Hasegawa et al 24 described a significant correlation of low reflective spaces in the RNFL with the presence of non-perfused areas on FA in RVO. It has been postulated that these spaces could be apoptotic changes in the RNFL due to retinal nonperfusion.…”
Section: Dovepressmentioning
confidence: 92%
“…First, in eyes with a large reduction in the macular VD, the number of capillaries decreases, which results in fewer leakages and may account for the lack of macular oedema 27 ; secondly, due to eyes with large macular non-perfused areas rapidly progress to a thinning of inner retina and result in reduction of oxygen consumption, which maintain balance between oxygen supply and consumption. 28 The above factors may cause less recurrence of macular edema in the resolved group.…”
Section: Research On the Role Of Octa In Following-up After Treatment...mentioning
confidence: 99%